2021
DOI: 10.3390/nu13124388
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Risk Factors of Poor Nutritional Status in Polish Elderly Population: The Results of PolSenior2 Study

Abstract: Poor nutritional status (PNS) threatens successful aging. Identifying potentially modifiable predictors of PNS is essential for elaborating a preventive strategy for the population at risk. To assess the prevalence of PNS in the Polish elderly population and analyze its socioeconomic correlates based on the data from the nationwide PolSenior2 project. Special emphasis was put on potentially modifiable factors among the identified PNS predictors. Nutritional status was assessed in 5698 community-dwelling older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…In old patients, loneliness is recognized as an independent factor associated with poor nutritional status. Old people show a greater risk of reduced social relationships, isolation at home, and fewer opportunities to socialize with other people [55,56]. Nutritional status is further affected by marital status since unmarried subjects present with a higher risk of malnutrition [57,58].…”
Section: Risk Factors For Malnutrition In Hospitalized Patientsmentioning
confidence: 99%
“…In old patients, loneliness is recognized as an independent factor associated with poor nutritional status. Old people show a greater risk of reduced social relationships, isolation at home, and fewer opportunities to socialize with other people [55,56]. Nutritional status is further affected by marital status since unmarried subjects present with a higher risk of malnutrition [57,58].…”
Section: Risk Factors For Malnutrition In Hospitalized Patientsmentioning
confidence: 99%
“…Poor nutritional status is an important lifestyle factor implicated in the etiology of body composition abnormalities. Impaired nutritional status in older adults may result from an inappropriate diet and socio-economic factors such as poverty or feelings of loneliness after the death of a spouse [ 13 , 14 ]. Older persons are at higher risk of impaired nutritional status [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect factors, such as low educational level and poverty, may lead to malnutrition by activating one of these three principal conditions. Sociodemographic characteristics are well-known predictors of such indirect factors, thus, some sociodemographic characteristics can predict malnutrition in older adults (Krzyminska-Siemaszko et al, 2021 ). A recent systematic review and meta analysis of 40 studies from various countries (Besora-Moreno et al, 2020 ) and 45 studies on Indian population (Kushwaha et al, 2020 ) assessing the risk of malnutrition in various older adult populations confirmed a strong relation between several socioeconomic factors (such as age, sex, educational level, marital status, income level, occupational level, place of residence, and region) and malnutrition or risk of malnutrition in older adults aged above 60.…”
Section: Introductionmentioning
confidence: 99%